THE USE OF MOBILE APPLICATIONS FOR ENHANCING VOCABULARY ACQUISITION AND SPEAKING PROFICIENCY (Web of Teachers: Inderscience Research, 2025)
The increasing integration of mobile technologies into education has transformed language learning practices, particularly in the development of vocabulary acquisition and speaking proficiency. Mobile applications provide flexible, learner-centered, and interactive environments that extend language learning beyond traditional classroom settings. This article examines the use of mobile applications as supportive tools for enhancing vocabulary development and speaking skills in language learning contexts. Drawing on existing literature, the study discusses different types of mobile applications, their pedagogical advantages, and their role in promoting learner autonomy, motivation, and engagement. In addition, potential challenges related to distraction, technological dependency, and pedagogical limitations are addressed. The findings suggest that when appropriately integrated into language instruction, mobile applications can effectively complement traditional teaching methods and contribute to improved vocabulary acquisition and speaking proficiency.